Front-End Processing for the CHiME-5 Dinner Party Scenario - Boeddeker, Christoph; Heitkaemper, Jens; Schmalenstroeer, Joerg; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. CHiME 2018 Workshop on Speech Processing in Everyday Environments, Hyderabad, India)
This contribution presents a speech enhancement system for the CHiME-5 Dinner Party Scenario. The front-end employs multi-channel linear time-variant filtering and achieves its gains without the use of a neural network. We present an adaptation of blind source separation techniques to the CHiME-5 database which we call Guided Source Separation (GSS). Using the baseline acoustic and language model, the combination of Weighted Prediction Error based dereverberation, guided source separation, and beamforming reduces the WER by 10:54% (relative) for the single array track and by 21:12% (relative) on the multiple array track.